Shaping subcellular tubes through vesicle trafficking: Common and distinct pathways. (15th January 2023) - Pradhan, R.; Urbieta-Ortiz, V.A.; Kumar, S.; Mathew, R.; Ríos-Barrera, L.D.
Abstract: Cells with subcellular lumens form some of the most miniature tubes in the tubular organs of animals. These are often crucial components of the system, executing functions at remote body locations. Unlike tubes formed by intercellular or autocellular junctions, the cells with junctionless subcellular lumens face unique challenges in modifying the cell shape and plasma membrane organization to incorporate a membrane-bound tube within, often associated with dramatic cellular growth and extensions. Results in the recent years have shown that membrane dynamics, including both the primary delivery and recycling, is crucial in providing the cell with the flexibility to face these challenges. A significant portion of this information has come from two in vivo invertebrate models; the Drosophila tracheal terminal cells and the C. elegans excretory cell. This review focuses on the data obtained from these systems in the recent past about how trafficking pathways influence subcellular tube and branching morphogenesis. Given that such tubes occur in vertebrate vasculature, these insights are relevant to human health, and we contrast our conclusions with the less understood subcellular tubes of angiogenesis.